DNA metabarcoding as a tool for invertebrate community monitoring: a case study comparison with conventional techniques. Issue 3 (15th January 2019) - Watts, Corinne; Dopheide, Andrew; Holdaway, Robert; Davis, Carina; Wood, Jamie; Thornburrow, Danny; Dickie, Ian A
Abstract: When conserving native biodiversity, it is particularly important to consider invertebrates, a diverse and functionally important component of biodiversity. However, their inclusion in monitoring and conservation planning has lagged behind larger fauna because collecting, sorting and identifying invertebrates using conventional monitoring techniques is often expensive, time consuming and restricted by expertise in diagnostics. Emerging DNA metabarcoding techniques could potentially revolutionise monitoring of invertebrates by providing the ability to characterise entire communities from a single, easily collected environmental sample. We aimed to characterise the invertebrate fauna of an isolated, coastal forest fragment in New Zealand using the same level of financial investment for conventional invertebrate monitoring (pitfall and malaise traps) and a DNA metabarcoding approach applied to two alternative sample types (conventional invertebrate samples and soil samples). The bulk invertebrate and soil DNA metabarcoding methods were able to reproduce ecological patterns observed in the beetle community detected using conventional sampling. The soil DNA metabarcoding method detected a different beetle community and a more diverse array of invertebrate taxa than conventional sampling techniques. DNA metabarcoding offers conservation managers a practical, cost‐effective technique for characterising whole invertebrate communities. However, increasing the taxonomic coverage of reference sequence databases (particularly for New Zealand invertebrates) through DNA barcoding efforts should be the focus of future research as it would improve the utility of metabarcoding methods for invertebrate monitoring, which would complement conventional techniques.